Polydatin Induces Apoptosis in Thyroid Cancer TPC-I Cells by Regulating Apoptotic Proteins and Downregulating JAK/ STAT Pathway - Zhao, Xiao; Gai, Kai; Lin, Bin (Indian Journal of Pharmaceutical Education and Research)
Background: Thyroid cancer is relatively uncommon but its incidence has been steadily increasing over the past years. The etiology of thyroid cancer is multifaceted, with both genetic and environmental causes playing major roles. Objectives: This work was devoted to explore the anticancer properties of the polydatin against papillary thyroid carcinoma TPC-I cells. Materials and Methods: The cytotoxicity of polydatin (at doses of 5-160 μM/mL) against thyroid cancer TPC-I cells were tested using the MTT assay. The endogenous ROS production and incidences of apoptosis was assessed using fluorescence staining assays. The concentrations of oxidative stress indicators were assessed utilizing assay kits. The concentrations of apoptotic and cell cycle proteins, including Bax, Bcl-2, cyclin D1, JAK-1, and STAT3 were assessed in the control and treated cells with appropriate assay kits. Results: The growth of thyroid cancer TPC-I cells was markedly diminished following treatment with polydatin at increasing concentrations. The polydatin treatment markedly increased ROS generation and induced apoptotic cell death in TPC-I cells. Furthermore, the polydatin treatment considerably increased TBARS levels and decreased antioxidant levels in TPC-I cells. In addition, polydatin treatment elevated the Bax protein level while diminishing the levels of cyclin D1, Bcl-2, JAK-1, and STAT3 proteins in TPC-I cells. Conclusion: The results of this work demonstrate that polydatin treatment considerably inhibits cell growth and promotes apoptosis in thyroid cancer TPC-I cells. Consequently, it possesses the potential to serve as an anticancer candidate to treat thyroid cancer.
Keywords: Cyclin D1; JAK/STAT pathway; Polydatin; Apoptosis; TPC-I cells.